Klasterisasi Perusahaan Sektor Energi Berdasarkan Rasio Kinerja Keuangan dengan Metode Fuzzy C-Means - Sriwirdani, Aisyah; Ahmad, Defri (JURNAL ILMIAH MATEMATIKA DAN TERAPAN, 2023)
The increasing number of companies on the Indonesia Stock Exchange means that there are more investment options for investors, causing investors to be confused about choosing the right company to invest in. Investors need to avoid mistakes in investing, one of which is by analyzing the company's financial performance ratios. In this study, companies in the open energy sector will be grouped based on financial performance ratios using the Fuzzy C-Means method. The results of this clustering can be used as material for consideration for investors wishing to invest in the open energy sector. The Fuzzy C-Means method is a method for grouping objects where the presence of cluster members is based on the degree of fuzzy membership. The ratios to be used are Earning per Share (EPS), Price Earning Ratio (PER), Return on Assets (ROA), Return on Equity (ROE), and Net Profit Margin (NPM). The number of clusters to be formed is 2 clusters. The calculation results obtained are that there are 46 companies in Cluster 1 and 22 companies in Cluster 2. Based on the analysis of cluster characteristics, cluster 2 is a cluster that contains companies with high financial ratios with the highest ratio value being Earning per share and net profit margin This means that the financial performance of companies in this cluster is quite good.